McDonald's Galleria a case study - De Guzman, John Henry L.; Cruz, Agerico V. (1993.)
The purpose of this study was to recommend an alternative design scheme for McDonald's Galleria. It took on the challenge to suggest alternative flooring, walls, furnitures, ceiling/lighting and exterior. The study was based on surveys conducted, interviews, observations and additional research by the author. Based on these, results were formulated. Findings showed that design elements should reflect careful consideration of their psychological impact. Failure to do so will be detrimental to the business.
Thesis (BID)--University of the Philippines Diliman.
Keywords: Fast food restaurants -- Interior decoration; McDonald's -- Philippines -- Pasig City